TREATMENT OF SEGMENTAL TIBIAL BONE LOSS BY DISTRACTION OSTEOGENESIS - Babar, Iqtidar Ullah; Afsar, Sardar Sohail; Gulzar, Mohammed (Journal of Postgraduate Medical Institute, 2012)
Objectives: To assess the clinical outcome of reconstruction of segmental tibial defects by the technique ofbone transport. Methodology: This prospective, quasi-experimental study was conducted in Lady Reading Hospital andprivate hospitals of Peshawar, Pakistan from October 2009 to September 2011. Segmental losses of tibialdiaphysis in 32 patients were 'regenerated' by bone transport. Results: Radiological results were excellent in 24 (75%), good in 3 (9%), fair in 4 (12%) and poor in 1(3%) patient. Clinical results were excellent in 19 (59%), good in 7 (22%), fair in 5 (16%) and poor in 1(3%) patient. During follow-up there were 9 obstacles of pin/wire infections and 7 problems whichrequired surgical intervention. At the last follow-up there were 6 true complications. The average fixatortime (external fixator index) was 25.9 weeks and the average bone healing time was 26.1 weeks. Conclusions: Distraction osteogenesis may be the best biological method of restoring the integrity of abone in segmental bone loss.